Review on risk factors, classification, and treatment of sternal wound infection - Song, Yaoyao; Chu, Wanli; Sun, Jiachen; Liu, Xinzhu; Zhu, Hongjuan; Yu, Hongli; Shen, Chuan’an (Journal of cardiothoracic surgery, 2023)
Sternal wound infection (SWI) is the most common complication of the median sternal incision. The treatment time is long, and the reconstruction is difficult, which causes challenges for surgeons. Plastic surgeons were often involved too late in such clinical scenarios when previous empirical treatments failed and the wound damage was relatively serious. Accurate diagnosis and risk factors against sternal wound infection need to be in focus. Classification of different types of sternotomy complications post-cardiac surgery is important for specific categorization and management. Not familiar with this kind of special and complex wound, objectively increasing the difficulty of wound reconstruction. The purpose of this comprehensive review is to review the literature, introduce various SWI risk factors related to wound nonunion, various classification characteristics, advantages and disadvantages of various wound reconstruction strategies, to help clinicians understand the pathophysiological characteristics of the disease and choose a better treatment method.